2010
DOI: 10.1002/sdr.432
|View full text |Cite
|
Sign up to set email alerts
|

Assessing individuals' understanding of nonlinear causal structures in complex systems

Abstract: Educators have provided anecdotal evidence that systems-oriented instruction improves students' ability to comprehend complex systems, but little research has been done to test this hypothesis. This article reviews past attempts to assess systems-oriented instruction and suggests the need for an assessment tool that can be implemented broadly but still provides a nuanced view of individuals' understanding of complex systems. A tool called Cognitive Mapping Assessment of Systems Thinking (CMAST) is presented as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 21 publications
0
90
1
9
Order By: Relevance
“…Subsequently, a more detailed classification scheme for the semantic information based on Kurtz dos Santos et al [36] and Plate [37] was developed. Concepts were divided into entities, attributes, quantities, and processes (landmarks were scored as a specific type of quantity), and their occurrences counted.…”
Section: Knowledge Content and Structure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a more detailed classification scheme for the semantic information based on Kurtz dos Santos et al [36] and Plate [37] was developed. Concepts were divided into entities, attributes, quantities, and processes (landmarks were scored as a specific type of quantity), and their occurrences counted.…”
Section: Knowledge Content and Structure Analysismentioning
confidence: 99%
“…To capture changes in knowledge structure in more detail, the web-like causality was assessed according to Plate [37]. Two measures were used.…”
Section: Knowledge Content and Structure Analysismentioning
confidence: 99%
“…Causal mapping is expected to foster the development of an appropriate mental model to support the problem solver in understanding the dynamics of complex systems (Huff 2002;Plate 2010) and to use this deeper understanding for a successful system control. Nevertheless, it remains unclear what kind of knowledge should be acquired through causal mapping, how participants can use and exploit the acquired knowledge for controlling a dynamic system and, as our study showed, under which conditions (e.g.…”
Section: Implications For Theorymentioning
confidence: 99%
“…In particular, modeling the causal structures of a problem is expected to foster the development of an appropriate mental model, to support the problem solver in understanding the dynamics of complex systems and to encourage holistic synthesis rather than reductive analysis (Huff 2002;Plate 2010;Sterman 2000). This assumption builds on the idea that humans make use of mental maps to represent their environment and to make predictions about it (Bryson et al 2004).…”
mentioning
confidence: 99%
“…A sufficient simulation could also be designed in a way that is meaningful to educators outside of the system dynamics community. This is a highly desired quality in systems thinking assessment [36] .…”
Section: Assessment Of Systems Thinkingmentioning
confidence: 99%